2007
DOI: 10.1590/s0066-782x2007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Índice de massa corporal e circunferência da cintura como marcadores de hipertensão arterial em adolescentes

Abstract: SummaryObjective: To evaluate the sensitivity and specificity of anthropometric measurements of body fat in a sample of Brazilian adolescents for the prediction of hypertension. Methods:th percentile for sex, age and height. A Results: A statistically significant correlation was observed between hypertension and the cutoff points considered Conclusion: population. As to BMI, the available cutoff points also showed a low level of sensitivity. There is a need to establish body fat cutoff points that can provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 20 publications
4
20
0
12
Order By: Relevance
“…In our study, we observed a significant association and correlation of BMI (according to some authors, it identifies excess weight, but not necessarily excess fat), TSF (a marker of excess body fat) and WC (marker of central deposition of excess body fat) among themselves and with blood pressure. Strong correlations between BMI and TSF 20,29 and between BMI and WC have been described 22,23 , supporting the findings of this study with respect to these variables.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, we observed a significant association and correlation of BMI (according to some authors, it identifies excess weight, but not necessarily excess fat), TSF (a marker of excess body fat) and WC (marker of central deposition of excess body fat) among themselves and with blood pressure. Strong correlations between BMI and TSF 20,29 and between BMI and WC have been described 22,23 , supporting the findings of this study with respect to these variables.…”
Section: Discussionsupporting
confidence: 88%
“…Rosa et al 23 , also using the same parameter 30 , evaluated 456 students aged 12 to 17 and demonstrated a significant association between hypertension and high WC.…”
mentioning
confidence: 99%
“…A recent study shows a low sensitivity of the cut-off points of these variables in detecting hypertension in adolescents 13 . However, studies like this, with a sample that enables the comparison of BP values according to the weight status and WC values, certainly contribute to provide data that show the gradual increase of the association of weight and increased WC with elevated BP.…”
mentioning
confidence: 95%
“…A circunferência de cintura (CC) foi aferida na metade entre a porção inferior da última costela e a borda superior da crista ilíaca, no final de uma A literatura já apontou a relação da medida de circunferência de cintura com fatores de risco cardiovascular, inclusive em adolescentes (ROSA et al, 2007). Quase 15% dos alunos, nesta pesquisa, apresentaram valores elevados de circunferência de cintura.…”
Section: Instrumentos E Procedimentosunclassified